Lina Bo Bardi e o desenho do móvel moderno para o Studio de Arte Palma - Coura, Fernanda Freitas (Farol, 2022)
This works about Lina Bo Bardi’s furniture design for Studio d’Arte Palma and how the architect managed combine local elements to her design, despite being a newcomer. The starting point to understand the reason behind Lina’s interest in rescuing cultural heritage was her life in Italy, from where she brought ideas that would be put into practice in Brazil. The knowledge she gained in her activities and alliances with other professionals in her birth country, in Brazil were combined to opportunities offered by urbanization and by the development of Brazilian modern architecture, which had reached international fame at that point.